Development study of Moringa oleifera Lam. seedlings cultivated in Paraíba (Research, Society and Development, 2022)
Moringa oleifera Lam. is a plant of Asian origin that grows in different morphoclimatic conditions, surviving with low water demand and high temperatures, conditions present in the State of Paraíba, Northeast region of Brazil. This study aimed to evaluate the development of Moringa oleifera Lam. seedlings cultivated in the municipality of Cuité, state of Paraíba (PB). During the first year of cultivation, morphometric characteristics of the plant such as height and diameter of the stem were evaluated and, after fruiting, the fruit was evaluated in relation to its length, thickness and number of seeds present per pod. It was also carried out the monitoring of the city's pluviometric index, soil pH and irrigation water. It can be observed that the pH of the soil under which the plants were cultivated varied between acid and slightly acid, with an annual rainfall between 50-150 mm in the region. The seedlings studied showed greater length, stem diameter and number of fruits than reported in the literature, indicating a favorable development in the climatic conditions presented in the municipality of Cuité-PB.